The transfer of two clades of Malaysian Sphenomorphus Fitzinger (Squamata: Scincidae) into the genus Tytthoscincus Linkem, Diesmos, & Brown and the description of a new Malaysian swamp-dwelling species - Grismer, L. Lee; Muin, Mohd Abdul; Wood, Perry L. Jr.; Anuar, Shahrul; Linkem, Charles W. (Zootaxa, 2016)
Phylogenetic analyses based on the mitochondrial gene ND2 and its flanking tRNAs indicate the diminutive upland and insular species Sphenomorphus bukitensis, S. butleri, S. langkawiensis, S. perhentianensis, and S. temengorensis form a monophyletic group that is phylogenetically embedded within the Southeast Asian genus Tytthoscincus. The analyses also indicate that a new swamp-dwelling skink from the Bukit Panchor State Park, Pulau Pinang, Peninsular Malaysia is the sister species to the swamp-dwelling species S. sibuensis from Pulau Sibu, Johor and Singapore and that these two are also embedded in the genus Tytthoscincus. By transferring the two Peninsular Malaysian clades of Sphenomorphus into the genus Tytthoscincus, the monophyly of the latter is maintained. The new species T. panchorensis sp. nov. can be distinguished from all other species of Tytthoscincus by having a unique combination of morphological and color pattern characteristics.